The form of eternity - Leite, Augusto Bruno de Carvalho Dias (Revista Archai, 2019)
According to the mythical-religious literature time is determined by the eternal nature of divinity or origin of all things. From this adagio, theological literature is provoked and studies on the eternal nature of divinity suggest that if the universe was created the image of its creator the first must also be eternal. Therefore the question arises: how to shape that which by nature is formless, infinite, namely eternity? To answer this question the following paper develops a brief history about the Judeo-Christian tradition on the problem of time and its relationship with eternity and also tries to prepare at the end one logical answer to the question about the form of eternity.